2003
DOI: 10.1002/bit.10891
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of apparent substrate selectivity of proteinase K encapsulated in liposomes through a cholate‐induced alteration of the bilayer permeability

Abstract: Proteinase K-containing liposomes with highly selective membrane permeability properties were prepared. The selectivity obtained was with respect to the two substrate molecules added to the external aqueous phase of the liposomes: acetyl-L-Ala-Ala-Ala-p-nitroanilide (Ac-AAA-pNA) and succinyl-L-Ala-Ala-Ala-p-nitroanilide (Suc-AAA-pNA). The liposome-forming lipid used was POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) and modulation of the membrane permeability was achieved using the detergent cholate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…4 C) (20,21). The fluorescent moieties of the PR constructs are only accessible to proteinase K in the extravesicular space, whereas the lipid bilayer acts as a diffusion barrier and prevents inward-facing moieties from digestion by proteinase K (22,23). The analysis of the fluorescence before and after digestion on an SDS-PAGE gel revealed that a vast majority of proteins were inserted in the predefined orientation.…”
mentioning
confidence: 99%
“…4 C) (20,21). The fluorescent moieties of the PR constructs are only accessible to proteinase K in the extravesicular space, whereas the lipid bilayer acts as a diffusion barrier and prevents inward-facing moieties from digestion by proteinase K (22,23). The analysis of the fluorescence before and after digestion on an SDS-PAGE gel revealed that a vast majority of proteins were inserted in the predefined orientation.…”
mentioning
confidence: 99%
“…In contrary, the permeability for small neutral molecules (like water, ammonia, urea, methanol) is high. A modulation of the vesicle membrane permeability can be achieved in different ways, for example by varying the vesicle shell composition, e. g. by simply varying the chain length of the lipids (Paula et al, 1996), by adding small amounts (at sub-solubilizing concentrations) of a micelle-forming surfactant (Treyer et al, 2002;Yoshimoto et al, 2004), thereby forming more permeable mixed vesicles. If the micelle-forming surfactant is in excess, however, the vesicles will be transformed into (mixed) micelles, accompanied by a complete release of the originally trapped aqueous content.…”
Section: Surfactant Aggregates As Compartmentsmentioning
confidence: 99%
“…phatidylcholine (PC) bilayers at sublytic concentrations [77], or ethanol [89] that causes the interdigitation of the two layers of a lipid bilayer [effectively causing the thinning of the bilayer (Fig. (6C)), as well as a significant increase in surface area], can enable the supply of encapsulated enzymes [77,90,91]. The membrane transport can occur in any direction, which depends on the direction of molecular gradients across the membrane.…”
Section: Substrate Delivery Into Vesicular Structuresmentioning
confidence: 99%